25. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS WITH CHRONIC PULMONARY ASPERGILLOSIS FUNGUS INFECTION UNDERGOING SURGERY AT NATIONAL LUNG HOSPITAL FROM 2020 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Background: Chronic pulmonary aspergillosis (CPA) is a chronic lung disease caused by Aspergillus fungus, commonly found in tuberculosis patients with cavitary sequelae of tuberculosis. The prevalence of CPA in Vietnam is high. CPA treatment includes two main methods: Antifungal treatment and surgery. This study was conducted with the objectives of describing the clinical and paraclinical characteristics of a group of patients with CPA undergoing surgery at the National Lung Hospital.Methods: Descriptive cross-sectional study. Subjects: Patients with CPA who underwent surgery at the National Lung Hospital from January 1, 2020 to December 31, 2022. Sampling method: Total population sampling. Information collecting method: Using medical records, processing data by SPSS software.Results: There were 126 patients included and studied. The average age of patients diagnosed with CPA in this study was 53 ± 13. The most common reason for hospital admission was hemoptysis which was 82% of the cases. The most common clinical symptom was hemoptysis (83%). History of pulmonary tuberculosis accounted for 61.1% of cases. The most common lesions on diagnostic imaging results are: Cavities (73.6%), aspergilloma (66.4%), and bronchiectasis (25.6%). Vascular abnormalities accounted for 40%, including abnormalities of bronchial arteries, internal/mammary/intercostal arteries, pulmonary arteries and are related to hemoptysis levels of patients.Conclusion: The group of CPA patients who underwent surgery at the National Lung Hospital often have a history of pulmonary tuberculosis, with hemoptysis as the main symptom, which was also the reason for hospital visit. The most common lesions on diagnostic imaging results were cavities accompanied by aspergilloma or intra-cavitary abnormalities, and bronchiectasis. Vascular abnormalities were encountered in 40% of cases and related to the condition and severity of hemoptysis of the patients.
Keywords: Chronic Pulmonary Aspergillosis, CPA, surgery.